PENINGKATAN LITERASI TENTANG ALAT PELINDUNG DIRI PADA PETANI PENGGUNA PESTISIDA (LINDUNG PENIDA) - Eliyana; Nafilah; Safira, Puspita Dinda; Febiani, Cika; Lutfa, Ianatul; Rokatun (Jurnal LENTERA, 2024)
The use of pesticides in husbandry is nothing new, it aims to increase agrarian products. Still, growers frequently don't use pesticides wisely, so the prevalence of poisoning due to pesticides is still high. One of the causes of high situations of poisoning is the low use of a particular defensive outfit. This low mindfulness is touched off by growers' lack of knowledge about the use of particular defensive outfits and the troubles of pesticides. This community service exertion aims to increase growers' knowledge about particular defensive outfits and pesticides. The conditioning was carried out in Gebang Anom Village, Rowosari District, Kendal Regency, Central Java for 3 days. The exertion begins by reviewing demographic data and measuring the original position of knowledge, also health education is handed. On the last day, another dimension was carried out regarding growers' knowledge about the use of particular defensive outfits and the troubles of pesticides. Data collection uses a questionnaire. After carrying out the analysis, the results showed that there was an increase in growers' knowledge by 27 percent about particular defensive outfits and the troubles of pesticides. Furnishing education can increase farmer's understanding so it's hoped that changes in stations regarding the use of particular defensive outfits can increase. Through this exertion, it's hoped that growers will be suitable to cover themselves from exposure and spot duly. Comprehensive and sustainable multisector collaboration can be a trouble to ameliorate farmer’s health.